2019
DOI: 10.1002/jcb.29297
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow macrophage M2 polarization and adipose‐derived stem cells osteogenic differentiation synergistically promote rehabilitation of bone damage

Abstract: By differentiating into and the balance being regulated between M1 (proinflammatory) and M2 (anti-inflammatory) heterogeneous populations, macrophages play critical roles during the host immune response in various physiological contexts in both health and diseases. Besides regulating innate and adaptive immune capacity, macrophages are also decisively involved in K E Y W O R D S adipose tissue-derived mesenchymal stem cells, bone marrow-derived macrophages, cell polarity, differentiation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 45 publications
0
30
0
Order By: Relevance
“…Increasing evidence indicated that MSCs could develop immunosuppressive properties by regulating the phenotypes and activities of innate and adaptive immune cells. In the microenvironment regulated by MSCs, T cells transformed into a tolerant Treg phenotype; macrophages transformed into an immunoregulatory M2-macrophages phenotype; NK cells transformed into non-free functional status, and MSCs could suppress the production of immunoglobulins and increase the production of regulatory B cells (Bregs) (31)(32)(33)(34). Cell-tocell contact dependent and independent ways to develop its' immunosuppression by blocking immune cell differentiation and cell cycle are described as the exact mechanisms (4,5,9,17).…”
Section: The Immunomodulatory Ability Of Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing evidence indicated that MSCs could develop immunosuppressive properties by regulating the phenotypes and activities of innate and adaptive immune cells. In the microenvironment regulated by MSCs, T cells transformed into a tolerant Treg phenotype; macrophages transformed into an immunoregulatory M2-macrophages phenotype; NK cells transformed into non-free functional status, and MSCs could suppress the production of immunoglobulins and increase the production of regulatory B cells (Bregs) (31)(32)(33)(34). Cell-tocell contact dependent and independent ways to develop its' immunosuppression by blocking immune cell differentiation and cell cycle are described as the exact mechanisms (4,5,9,17).…”
Section: The Immunomodulatory Ability Of Stem Cellsmentioning
confidence: 99%
“…Ligand type Target cells Disease or microenvironment References ICAM-1 LFA-1 Macrophage T cells Microglia DC cells Neutrophils T cell Ag receptor' activated CD3+ pan-T cells activation (41) Autoimmune thyroiditis (6) Bony defect (32) Improve cerebral infarction (3,48) Alzheimer's disease (15) Multiple sclerosis (49) Ischemic stroke (50) Galectin-9 (sGal-9) TIM-3 T cells DC cells Macrophage αCD28/OKT3-activated PBMC (60) Hepatocyte chronic infection caused by HCV (63) Chronic HCV infection and promote immunotolerance (64) GVHD (16,45,65) Autoimmune diabetes in NOD mice (66) Autoimmune cholangitis (67) Multiple sclerosis (68) PHA activated PBMC (69) Normal PBMC or abortion-PBMC 70LPS-Induced Preeclampsia-Like Impairment (72) LPS-induced M1-macrophage (73) Experimental hypersensitivity pneumonitis (71) Galectin-1 sGal-1 T cells PHA-stimulated PBMC (76) Ovalbumin-induced DTH model (76) Free-serum in α-MEM essential medium (80) Mice injected orthotopically with breast carcinoma cells or subcutaneously with melanoma cells (81,83) Galectin-3 sGal-3 T cells Induced medium which contained L-DMEM, 5% FBS, VEGF (10 ng/mL), and bFGF (2 ng/mL)…”
Section: Receptor Typementioning
confidence: 99%
“…Macrophage is a critical component of the immune system, diffusely distributed in the body, expressing various bioactive substances, receptors and enzymes [5]. M2 macrophage ordinarily triggers cell proliferation, extracellular matrix synthesis and tissue remodeling [6]. A study has reported that M2 phenotype macrophages secret transforming growth factor-β1 to promote the migration and stemness of glioma cells [7].…”
Section: Introductionmentioning
confidence: 99%
“…To effectively repair bone defects duo to tumour resection, bone biomaterials should provide appropriate media for angiogenesis and osteogenesis (29). In vitro, M2 macrophages directly regulate osteogenic differentiation of bone marrow mesenchymal stem cells (30,31). The mechanism may be due to proregenerative cytokines produced by M2 macrophages, such as TGF-β, VEGF, Ang-1 and IFG-1 (32).…”
Section: Introductionmentioning
confidence: 99%